MÁHÁLLENIŃ JASLAR TÁRBIYASÍNDAǴÍ ORNÍ - Pirniyazova, M. (SCIENCE and SOCIETY, 2025)
The article talks about the place and role of the neighborhood in raising the spirituality of young people at the current stage of society's development.